2019
DOI: 10.1124/jpet.118.254516
|View full text |Cite
|
Sign up to set email alerts
|

Cinobufacini Ameliorates Dextran Sulfate Sodium–Induced Colitis in Mice through Inhibiting M1 Macrophage Polarization

Abstract: Cinobufacini is a traditional Chinese medicine used clinically that has antitumor and anti-inflammatory effects. It improves colitis outcomes in the clinical setting, but the mechanism underlying its function yet to be uncovered. We investigated the protective effects and mechanisms of cinobufacini on colitis using a dextran sulfate sodium (DSS)-induced colitis mouse model, mainly focusing on the impact of macrophage polarization. Our results showed that cinobufacini dramatically ameliorated DSS-induced coliti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 32 publications
1
23
0
Order By: Relevance
“…Activated macrophages are functionally divided into two main categories: the M1 type (the classical-activated macrophage) and the M2 type (the alternatively activated macrophage) (11). Although M1-type macrophages release proinflammatory cytokines and enhance inflammatory responses, they also cause injury to host tissue (12). On the contrary, M2-type macrophages release antiinflammatory cytokines and help maintain tissue immune homeostasis, thus avoiding overactive inflammation (13,14).…”
Section: Introductionmentioning
confidence: 99%
“…Activated macrophages are functionally divided into two main categories: the M1 type (the classical-activated macrophage) and the M2 type (the alternatively activated macrophage) (11). Although M1-type macrophages release proinflammatory cytokines and enhance inflammatory responses, they also cause injury to host tissue (12). On the contrary, M2-type macrophages release antiinflammatory cytokines and help maintain tissue immune homeostasis, thus avoiding overactive inflammation (13,14).…”
Section: Introductionmentioning
confidence: 99%
“…Cinobufacini (Huachansu), an aqueous extract from the skin of the Bufo toad, is a traditional Chinese medicine widely used in clinic with anti-tumor and anti-inflammatory effects[10]. In previous study, our team found that cinobufacini could relief DSS-induced colitis in mice[11], but the underlying mechanism is still elusive. Bufadienolides, the principal bioactive components of cinobufacini, have been reported to have strong antimicrobial activity in vitro[12].…”
Section: Introductionmentioning
confidence: 99%
“…The liver tissues sections were deparrafinized and antigen retrieval were also performed as previously described 19 . MaxVision HRP-Polymer antiRabbit IHC Kit (MXB Biotechnologies, Fuzhou, China) was used to develop signal.…”
Section: Methodsmentioning
confidence: 99%
“…The protein extraction method was according to our previous study 19 , 22 . Equal amounts of proteins were separated by sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE).…”
Section: Methodsmentioning
confidence: 99%